2015
DOI: 10.1111/1471-0528.13607
|View full text |Cite
|
Sign up to set email alerts
|

Brain sparing effect in growth‐restricted fetuses is associated with decreased cardiac acceleration and deceleration capacities: a case–control study

Abstract: Brain sparing in IUGR fetuses is associated with decreased acceleration and deceleration capacities of the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…Interestingly, recent reports involving other non-invasive abdominal FECG systems have shown promising results for the use of phase-rectified signal averaging measurements (PRSA) and fetal heart rate variability (FHRV) in IUGR fetuses (Stampalija et al, 2015a,b). PRSA signals are representative of the current maturation status of the fetal autonomic nervous system (ANS) where lower acceleration capacity (AC) and deceleration capacity (DC) signals have been observed in IUGR fetuses with or without brain sparing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent reports involving other non-invasive abdominal FECG systems have shown promising results for the use of phase-rectified signal averaging measurements (PRSA) and fetal heart rate variability (FHRV) in IUGR fetuses (Stampalija et al, 2015a,b). PRSA signals are representative of the current maturation status of the fetal autonomic nervous system (ANS) where lower acceleration capacity (AC) and deceleration capacity (DC) signals have been observed in IUGR fetuses with or without brain sparing.…”
Section: Discussionmentioning
confidence: 99%
“…PRSA signals are representative of the current maturation status of the fetal autonomic nervous system (ANS) where lower acceleration capacity (AC) and deceleration capacity (DC) signals have been observed in IUGR fetuses with or without brain sparing. One study found a significant association between either AC and DC and the middle cerebral artery pulsatility index (PI; p = 0.01; p = 0.005) (Stampalija et al, 2015a). With FHRV, short term variability (STV) evaluation is known to reflect the status of the fetal oxygen supply, therefore indicating the fetal acid-base status.…”
Section: Discussionmentioning
confidence: 99%
“…In the obstetrical field, DC was able to identify a lower ANS reactivity in IUGR fetuses, and proved to be superior to short term variability in discriminating IUGR fetuses from controls [22][23][24]. Furthermore, we previously observed that the DC of the fetal heart, derived from PRSA analysis of fetal ta-ECG in IUGR fetuses from 25 weeks of gestation to term, was associated with middle cerebral artery pulsatility index, a consistent index of brain sparing adaptation [25]. The analysis of maternal ECG recorded trans-abdominally could be challenging due to the signal-to-noise ratio.…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…(Rivolta et al, 2014) Even more interestingly, it has been shown that IUGR fetuses with brain sparing (fetal adaptive mechanism to chronic hypoxemia) have a lower acceleration and deceleration capacities than growth restricted foetuses without brain sparing. (Stampalija et al, 2016) This intimate inter-relation between brain perfusion and FHR is thought to be mediated via ANS (aortic chemoreceptors and carotid baro-and chemoreceptors). Newer data also show an activation of ANS in fetuses affected by maternal gestational diabetes which could not be seen using conventional techniques.…”
Section: A)mentioning
confidence: 99%